2023
DOI: 10.1021/acsami.2c23013
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microstructures in the Dielectric Properties of PVDF-Based Nanocomposites Containing High-Permittivity Fillers for Energy Storage

Abstract: Polymer-based nanocomposites containing inorganic ferroelectric inclusions, typically ABO3 perovskites, have emerged as innovative dielectric materials for energy storage and electric insulation, potentially coupling the high breakdown strength (BDS) and easy processing of polymers with the enhancement of dielectric constant provided by the ferroelectric phase. In this paper, experimental data and three-dimensional finite element method (3D FEM) simulations were combined to shed some light on the effect of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The SEM image of the TiO 2 particle agglomerates is shown in Figure S5, which shows the agglomerates with diameters of about 200 nm. It has been shown that due to the principle of incompatibility at the organic\inorganic interface, the mass accumulation of inorganic fillers causes significant structural defects at the organic/inorganic interface of the hybrid film, resulting in considerably decreased insulation capability, which will eventually reduce the ability of the combined material to store energy. …”
Section: Resultsmentioning
confidence: 99%
“…The SEM image of the TiO 2 particle agglomerates is shown in Figure S5, which shows the agglomerates with diameters of about 200 nm. It has been shown that due to the principle of incompatibility at the organic\inorganic interface, the mass accumulation of inorganic fillers causes significant structural defects at the organic/inorganic interface of the hybrid film, resulting in considerably decreased insulation capability, which will eventually reduce the ability of the combined material to store energy. …”
Section: Resultsmentioning
confidence: 99%
“…The polarization in the PVDF matrix gradually increases with increasing filler loading up to 5 wt % and then decreases dramatically for filler quantities greater than 5 wt %. The addition of more CsPbI 3 to the composite promotes interactions among themselves, resulting in percolative pathways, and after a certain wt % of CsPbI 3 (>5 wt %), the loop area decreases. …”
Section: Resultsmentioning
confidence: 99%
“…5,19 Therefore, this kind of core@shell structured particle is regarded as the good strategy for accomplishing the balance between the high ε and E b as well as low loss in polymers. [20][21][22][23][24] As one kind of one-dimensional semiconductor nanomaterials, β-silicon carbide whiskers (β-SiC w ) with a large aspect ratio and excellent overall properties like high mechanical modulus and strength, as well as large TC had been widely used in various occasions. 25,26 Upon approaching the f c , the β-SiC w /polymers exhibit a concurrent increase in both the ε and TC, which are unfortunately accompanied with the appearance of leakage current and a large loss.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the insulating shells like dielectric ceramics with a medium ε usually covering on the fillers' superficies can effectively assuage the permittivity mismatch between the matrix and the filler, thus lessening the maldistribution electric field or distortion throughout the composites, thus enhancing high‐field endurance 5,19 . Therefore, this kind of core @ shell structured particle is regarded as the good strategy for accomplishing the balance between the high ε and E b as well as low loss in polymers 20–24 …”
Section: Introductionmentioning
confidence: 99%